Spanish students’ categorical perceptions of feminist movements - Ávila-Muñoz, Antonio Manuel (Springer, 2024)
Identifying a society’s perceptions and, by extension, opinions of a certain social move- ment can help to understand to what extent the movement has been successful in effect- ing change. When working to gain such an understanding, a focus on the student popula- tion is essential, as their opinions provide insight into the future conditions of society and, thus, into whether the movement has been successful in effecting lasting social change. The present work focusses on the feminist movements and, in line with the above, analyses the perceptions held by a sample of 600 Spanish students enrolled in compulsory second- ary, pre-university, and university education. The method employed begins with the use of association tests to extract lexical networks. Then, following a theoretical transformation, the traditional lexical availability index is applied in combination with fuzzy set theory to the sample of lists obtained so as to map the structure of the collective network, a novel approach that results in different levels of compatibility. The highest levels of compatibil- ity reveal the prototypical conceptualisation as well as the sample’s shared cognitive per- ception. The results suggest that although the population under study may have absorbed the feminist movements’ messages of equality and respect, distorted perceptions could still remain in certain groups analysed. This work therefore recommends that education centres may wish to consider communicating objective information on the feminist movements specifically to women, as this could ultimately lead to all students fully embracing a femi- nist awareness distanced from extreme ideologies
Keywords: Feminismo; Percepción social; Feminist movements; Feminism; Students; Shared perceptions; Lexical associations